Pengenalan Aksara Bali Pada Anak Usia Dini Melalui Media Gambar dan Mewarnai - I Wayan Agus Gunada; Ida Bagus Alit Arta Wiguna; I Made Ardika Yasa; Ni Luh Drajati Ekaningtyas; Ni Komang Wiasti; Anak Agung Istri Anom; Ni Made Dwi Utari; Ni Putu Witari Putri; Ni Nyoman SInar Widia Swari; Sri Sofiana Amni (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2022)
This article aims to describe the process of introducing Balinese script to early childhood at PAUD Mutiara Rinjani in Selelos Village. Balinese script is part of Balinese culture and an essential part of Hindu religious rituals. Still, in reality, not all children can get to know and learn Balinese script, especially Balinese children outside the island of Bali. This makes it essential to introduce the Balinese script early so that community service activities become a necessary learning process. This community service activity is carried out with a community-based approach which is carried out with the planning, implementation, and evaluation stages. Based on the results of data during the activity, it can be concluded that quite essential things are the introduction of Balinese script activities carried out through the media of coloring books compiled by the activity coach, the emphasis of learning is only on the realm of knowing, the training runs smoothly. The children are enthusiastic about the introduction process, which is carried out pleasantly through the media of images. It is hoped that similar activities can be carried out again so that the training context is sustainable. It is expected that the description of this activity can be important information and a reference in planning a service program related to the introduction and learning of Balinese script for early childhood.